Optimization of the power conversion efficiency in high bandgap pyridopyridinedithiophene-based conjugated polymers for organic photovoltaics by the random terpolymer approach. (June 2017) - Gedefaw, Desta; Sharma, Anirudh; Pan, Xun; Bjuggren, Jonas M.; Kroon, Renee; Gregoriou, Vasilis G.; Chochos, Christos L.; Andersson, Mats R.
Graphical abstract: Highlights: An alternating (P1) and a random terpolymer (P2) are reported. The random terpolymer showed a better miscibility with PCBM giving smooth surface. The random terpolymer showed a 70% increase in the photovoltaic performance. The random terpolymer allows to delicately engineer the properties of polymers. Abstract: We report that the organic photovoltaic (OPV) performance of wide band gap pyridopyridinedithiophene-based conjugated polymers can be significantly improved by employing the random terpolymer approach for the development of new pyridopyridinedithiophene-based conjugated polymers. This is demonstrated by the synthesis of the alternating copolymer (P1) consisting of 3, 3′-difluoro-2, 2′-bithiophene and pyridopyridinedithiophene and the random terpolymer (P2) containing pyridopyridinedithiophene 3, 3′-difluoro-2, 2′-bithiophene and thiophene. OPV devices fabricated by P1 and P2 in combination with PC61 BM and PC71 BM in an inverted device configuration exhibited power conversion efficiencies (PCEs) of 1.5% and 4.0%, respectively. We identified that the main reason for the enhanced performance of the OPV devices based on the P2 random copolymer was the improved morphology (miscibility) between P2 and PCBM as compared to P1. More specifically, atomic force microscopy (AFM) and scanning electron microscopy (SEM) studies revealed that the P1 based films showed rougher surface with clear crystallization/precipitation of the polymer chains even after the addition of chloronaphthalene (CN) to the chloroform processing solvent which significantly limited the short circuit current density (JSC ), fill factor (FF) and overall performance of the prepared photovoltaic devices. On the other hand, P2 based films showed better miscibility with the acceptor particularly when processed using 5% CN containing chloroform solvent giving a respectable improvement in the PCE of the photovoltaic devices.